ITE Law Enforcement Against Plagiarism of Scientific Works on Academic Platforms: Challenges and Solutions - Syahril, Muh. Akbar Fhad; Zaid, M.; Karović, Sadmir (Jurnal Litigasi Amsir, 2024)
This study examines law enforcement against the crime of plagiarism of scientific papers on online academic platforms from the perspective of the ITE Law and related regulations. The research method used is normative juridical with a legislative approach. The results of the study show that the crime of plagiarism in the digital era has been regulated by various laws and regulations. However, there are still challenges in its implementation. Harmonization and synchronization of laws are needed to overcome overlapping and legal gaps. Effective law enforcement efforts require a comprehensive approach involving legal, technological, and socio-cultural aspects. This study concludes that regulatory harmonization, increased coordination between institutions, the development of plagiarism detection technology, and the strengthening of anti-plagiarism culture are needed to realize academic integrity in the digital era.